The guiding principles governing the labour inspection system - Toledo Toribio, Omar (2007)
The present article studies the principles of legality, primacy of the reality,impartiality and objectivity, fairness, technical and functional autonomy, hierarchy, effectiveness, unit of function and performance, confidentiality, loyalty, professional probity, professional confidentiality, honesty and speed, all of it because of the Law N° 28806, General Law of Inspection of Work, has anticipated them like principles that govern the System of Inspection of Work